تطوير أداء ترميز الشبكة الخطي العشوائي لتحسين النقل الموثوق في الشبكات اللاسلكية متعددة القفزات - حجازية محمد; إبراهيم أحمد (Latakia University Journal -Engineering Sciences Series, 2018)
يعد ترميز الشبكة الخطي العشوائي RLNC)) تقنية حديثة تستخدم لتحسين أداء الشبكات اللاسلكية ذات الضياع، ويكون لهذا التحسين أهمية كبيرة في حالات الإرسال المتعدد وفي الشبكات اللاسلكية متعددة القفزات. لكن، لا يزال هذا الترميز يعاني من نقاط ضعف أساسية تقلل من أدائه. أبرزها مشكلة الارتباط الخطي بين الرزم المرمزة، وعملية التحقق من استقلالية هذه الرزم خطياً، إضافة إلى الحمل الإضافي لترويسة الرزم المرمزة. سنقدم في هذا البحث آلية عمل منظمة لعملية ترميز الشبكة الخطي العشوائي تسمى ORLNC، تطبق في العقد المصدر من الشبكات اللاسلكية متعددة القفزات. تعتمد هذه الآلية على توليد رزم مرمزة مستقلة خطياً وفق مبدأ مصفوفة Vandermonde بعد تحديد حجم حقل غوص المناسب لعملية الإرسال المطلوبة، فيتم حل مشكلة الارتباط الخطي لهذه الرزم وكذلك يتم التقليل من حجم ترويستها إلى أدنى حد. فقط عملية إعادة الترميز في العقد المتوسطة من هذه الشبكات تتم وفق آلية الترميز التقليدية (RLNC). الهدف الأساسي هو تحقيق أفضل استفادة من عرض الحزمة مع المحافظة على فعالية النقل الموثوق في هذه الشبكات. Random Linear Network Coding (RLNC) is considered a new technology that is used to enhance the performance of prone losses wireless networks; this enhancement has a big advantage in multicast scenarios and in multi hop wireless networks. However, this coding still suffer from major weak points that reduce its performance, basically the linear dependency between coded packets, and the confirming operation of the linear independency for these packets, in addition to the header overhead of the coded packets. In this research, we will present an organized mechanism of the random linear network coding process called ORLNC, implemented in the source node of multi hop wireless networks. This mechanism depends on generating independent coded packets according to Vandermonde matrix, after determining the convenient size of Galois field for required transmission process. Which solves the problem of linear dependency and reduce the header overhead of the coded packet to the minimum size. Only recoding process at intermediate nodes of these networks is done according to the traditional coding mechanism (RLNC). The main purpose is to achieve the best utilization of bandwidth with keeping the efficiency of reliable transfer of these networks.